2020
DOI: 10.3389/fmicb.2020.01992
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Dynamics Imbalance: A Strategy for Promoting Viral Infection

Abstract: Mitochondria are highly dynamic organelles that maintain the dynamic balance of splitfusion via kinetic proteins. This maintains the stability of their morphological functions. This dynamic balance is highly susceptible to various stress environments, including viral infection. After viral infection, the dynamic balance of the host cell mitochondria is disturbed, affecting the processes of energy generation, metabolism, and innate immunity. This creates an intracellular environment that is conducive to viral p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(60 citation statements)
references
References 107 publications
1
59
0
Order By: Relevance
“…In addition, there are other receptormediated pathways leading to mitophagy including BCL2 and adenovirus E1B 19kDa interacting protein 3 (BNIP3), Nip3-like protein X (NIX)/BNIP3L, FUN14 domain containing protein 1 (FUNDC1), and optineurin (OPTN). Multiple viruses have gained various strategies to counteract the antiviral mechanisms by controlling mitochondrial quality and content (Zhang et al, 2018;Ren et al, 2020). A recent study by Sin et al showed that CVB3 promotes mitochondrial fragmentation and uses mitophagosomes to release extracellular microvesicles to promote viral dissemination (Sin et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there are other receptormediated pathways leading to mitophagy including BCL2 and adenovirus E1B 19kDa interacting protein 3 (BNIP3), Nip3-like protein X (NIX)/BNIP3L, FUN14 domain containing protein 1 (FUNDC1), and optineurin (OPTN). Multiple viruses have gained various strategies to counteract the antiviral mechanisms by controlling mitochondrial quality and content (Zhang et al, 2018;Ren et al, 2020). A recent study by Sin et al showed that CVB3 promotes mitochondrial fragmentation and uses mitophagosomes to release extracellular microvesicles to promote viral dissemination (Sin et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Viruses could modulate MD in order to favour their intracellular survival or elude host immunity. Hence, the interplay between MD and viral pathogenesis represents a novel antiviral strategy [41]. The impact of Flavivirus infection on the MD has been mainly focused on DENV.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, mitochondrial fission is considered a prerequisite step for mitophagy (Mizushima et al, 2002;Rambold et al, 2011;Pernas and Scorrano, 2016;Burman et al, 2017). In response to the apical role of the mitochondria in antiviral immunity and the critical role of fusion and fission in maintaining mitochondrial health and function, viruses have developed a range of strategies to influence mitochondrial dynamics and promote their own proliferation and persistence in the cell (Ren et al, 2020).…”
Section: Maintenance Of Mitochondrial Homeostasismentioning
confidence: 99%
“…Mitochondria are susceptible to the multifaceted effects of viral infection, either by direct attack of virus-encoded proteins or by regulation of infection-induced changes in cellular conditions. Therefore, maintaining a balance between mitochondrial fusion, fission, and the proper function of mitophagy is important for cells to cope with viral infections (Ren et al, 2020). Studies have shown that some viruses can manipulate various steps of the molecular machinery of mitophagy for their own benefit (Figure 2).…”
Section: Triggering Of Mitophagy During Viral Infectionmentioning
confidence: 99%